Insulin resistance: Review of the underlying molecular mechanisms - Yaribeygi, Habib; Farrokhi, Farin Rashid; Butler, Alexandra E.; Sahebkar, Amirhossein (Journal of cellular physiology, 2019)
Most human cells utilize glucose as the primary substrate, cellular uptake requiring insulin. Insulin signaling is therefore critical for these tissues. However, decrease in insulin sensitivity due to the disruption of various molecular pathways causes insulin resistance (IR). IR underpins many metabolic disorders such as type 2 diabetes and metabolic syndrome, impairments in insulin signaling disrupting entry of glucose into the adipocytes, and skeletal muscle cells. Although the exact underlying cause of IR has not been fully elucidated, a number of major mechanisms, including oxidative stress, inflammation, insulin receptor mutations, endoplasmic reticulum stress, and mitochondrial dysfunction have been suggested. In this review, we consider the role these cellular mechanisms play in the development of IR.